Electrochemical sensing in telemedicine (a review) - Badea, Mihaela; Idomir, Mihaela; Florescu, Monica; Rogozea, Liliana (Univerzita Pardubice, 2011)
Telemedicine aims to use telecommunication systems (transmitting data, documents and other information) for more rapid interventions, diagnostic and treatment decisions and medical recommendations. Electrochemical sensors could be useful to improve the practice of medicine over the distance, helping the general practitioners and the emergency doctors to apply good and rapid procedures, to monitor chronic situation for several patients (by quantification of biomarkers and specific compounds related to their medical condition).
Keywords: electrochemical sensors; telemedicine; review